Математическое моделирование синхронной реактивной машины - Калюжный, Константин Александрович; Волянский, Роман Сергеевич; Садовой, Александр Валентинович (НТУ "ХПИ", 2013)
Approximation of experimentally captured dependencies Lk = f(θ,ik) are performed. Analytical expressions, taking into account the saturation induction, are found. The mathematical model of six-phase synchronous reluctance machine ШД-5Д1МУ3 are simulated. The analysis of the obtained transients is shown.
Keywords: применение СРМ; достоинства СРМ; прецизионные электроприводы; индуктивность фазной обмотки статора